Evaluating drought tolerance in marigold cultivars across different soil moisture levels - YASHESHWAR; KUMAR, MUKESH; RANI, ANITA; UMAR, SHAHID (Journal of Soil and Water Conservation, 2024)
This research delves into the effects of various soil moisture strategies on the performance of different cultivars of marigold, focusing on the number of flowers (NoF), flower yield (FY), and proline content. Cultivars of Tagetes erecta include ‘pusa narangi genda’, ‘pusa basanti genda’, T. erecta ‘Inca’, T. erecta Vanilla’, ‘marigold hawaii orange’ while T. patula cultivars were ‘queen sophia’, ‘red brocade’, ‘dainty marietta’, ‘marigold gulzafri yellow’, ‘marigold gulzafri orange’, ‘valentia yellow’, ‘pusa arpita’ and ‘bolero red’. Under normal conditions, T. erecta cultivars exhibited an average of 56.99 flowers per plant, with moderate deficit irrigation (MDI) and severe deficit irrigation (SDI) resulting in 19.37% and 54.92% reductions in NoF, respectively. A corresponding decline in flower yield of 31.01% in MDI and 64.80% in SDI was observed compared to the control. WDSI analysis pinpointed C2 as suitable for deficit irrigation based on its flower yield response. Proline content increased by 62.3% and 65.5% in MDI and SDI, respectively, compared to the control. The WDSI for proline content guided the selection of C2 for further experimentation. In conclusion, this study not only highlights variations in floral parameters and proline content under diverse irrigation conditions but also emphasizes the suitability of cultivar C2 for soil moisture stress to its favorable responses across multiple parameters. Additionally, the study extends to T. patula cultivars (C1-C8), revealing that C1, among all cultivars, exhibited a WDSI value less than 1 under both water stress conditions for flower yield.